2015
DOI: 10.1016/j.corsci.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Performance of chromia- and alumina-forming Fe- and Ni-base alloys exposed to metal dusting environments: The effect of water vapor and temperature

Abstract: a b s t r a c tFe-and Ni-base alloys including an alumina-forming austenitic alloy were exposed for 500 h under metal dusting environments with varying temperature, gas composition and total pressure. For one H 2 -CO-CO 2 -H 2 O environment, the increase in temperature from 550 to 750°C generally decreased metal dusting. When H 2 O was added to a H 2 -CO-CO 2 environment at 650°C, the metal dusting attack was reduced. Even after 5000 h at a total pressure of 9.1 atm with 20%H 2 O, the higher alloyed specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…One large difference in gas composition is the water vapor level, much higher at HP. The reduction of metal dusting degradation by the addition of H 2 O is well known and has already been observed [3,[16][17][18][19]. However, the contrary is observed in the present work, i.e.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…One large difference in gas composition is the water vapor level, much higher at HP. The reduction of metal dusting degradation by the addition of H 2 O is well known and has already been observed [3,[16][17][18][19]. However, the contrary is observed in the present work, i.e.…”
Section: Resultscontrasting
confidence: 59%
“…To this end, carbon activity is generally used to define metal dusting conditions. However, a given carbon activity can be obtained from very different conditions of pressure, temperature and gas mixture [2,3]. To better understand what governs the severity of metal dusting, two experiments were carried out on two austenitic commercial alloys, 800HT and HR120, for more than 6000 h. They were performed at the same temperature, similar carbon activities and oxygen partial pressures but with different total pressures and gas velocities.…”
Section: Introductionmentioning
confidence: 99%
“…Austenitic stainless steels with relatively high Cr and Ni, on the other hand, can be used in higher temperatures due to their combination of relatively good creep strength and high temperature oxidation resistance [9]. Extensive studies [10][11][12][13][14][15][16][17][18][19] in recent years on the oxidation of austenitic stainless steels (e.g. 304, 310) in wet gases have reported the breakaway oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown that after thermal exposure in atmospheres containing CO, CO 2 , hydrocarbon gases like CH 4 , and C 2 H 4 , the conventional Cr-containing steel or heat-resisting alloys are readily susceptible to an internal carburization attack [29][30][31][32][33][34][35], while protective external chromia scales are difficult to develop. In a CH 4 -H 2 plasma environment, the carbon activity can be described using an equilibrium reaction:…”
Section: Resultsmentioning
confidence: 99%